Tracing the Intellectual Legacy of Da’wah and Islamization in Nusantara: A Bibliometric and Historical Study - Arik Dwijayanto; Muhammad Choirin (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study examines the intellectual and historical development of da’wah and Islamization in Nusantara, emphasizing key scholarly contributions, academic trends, and influential periods. By employing advanced bibliometric methods, this research systematically maps the evolution of da’wah, identifying seminal works, leading scholars, and dominant themes that have shaped its discourse. The findings reveal critical shifts in da’wah strategies, the roles of various actors in propagating Islam, and the socio-political dynamics influencing these processes. Furthermore, the study underscores the contemporary relevance of historical scholarship in refining modern da’wah methodologies, ensuring their adaptability and effectiveness. By highlighting how past scholarly contributions have shaped da’wah practices, this research provides a robust academic foundation and a strategic framework for future studies, fostering a deeper understanding of Islam’s intellectual and cultural legacy in Nusantara.